Keragaman Gen K-Kasein dan Hubungannya dengan Produksi dan Kualitas Susu pada Domba di Unit Pendidikan dan Penelitian Peternakan (UP3) Jonggol - Cece Sumantri; Eryk Andreas; Achmad Farajallah; Jarmuji Jarmuji (Institut Pertanian Bogor, 2008)
The objectives of this study were to identify polymorphisms in ovine K-casein gene exon 4 and its association with milk yield, percentage of protein and milk fat in sheep under extcnsif management at JASTRU (Jonggol Animal Studies Teaching and Research Unit) farm, Fact. of Anim Sci, Bogor Agric. University. The 83 blood sample from ewes which have record of milk production were used to determined polymorphism by using PCR-SSCP (Polymerase Chain Reaction-Single Strand Conformation Polymorphism) methode. The research activities were carried out through blood collection, DNA isolation, and fragment DNA amplification by PCR and separation in electrophoresis with silver staining. Electrophoretic pattern (PCR-SSCP) revealed th rce types of K-casein gene were dcsignitcd A, Band C type. The highest proportion was A type 69.57% and followed hy B 28.99% and the lowest C 1.45%. The were no significant effect of types of of K-casein gene on milk production and milk quality (percentage of protein and fat) in local sheep from Jonggol. Keywords: .Jonggol sheep, K-cascin gcn, PCR-SSCP, polymorphism